Pembelajaran Daring dan Manajemen Waktu Terhadap Prestasi Akademik Mahasiswa Pada Masa Pandemi Covid-19 - Rindy Antika Kurniati; Sudarno Sudarno; Feri Setyowibowo (Jurnal Pendidikan Ekonomi (JUPE), 2023)
This study has a purpose, namely to determine the effect of online learning on academic achievement, time management on academic achievement, and the effect of online learning and time management on academic achievement simultaneously. The object of this research is FKIP UNS 2018 students as many as 1906 students. Sampling using purposive random sampling, as many as 331 samples. Collecting data using a questionnaire. Multiple regression analysis was used for data analysis techniques. The results of this study include (1) there is a simultaneous positive and significant effect between online learning and time management on academic achievement during the Covid-19 pandemic. (2) There is a positive and significant partial effect between online learning on academic achievement during the Covid-19 pandemic. (3) There is a positive and significant partial effect between time management on academic achievement during the Covid-19 pandemic.